Cancer and Covid-19: Collectively catastrophic. (February 2022) - du Plessis, M.; Fourie, C.; Riedemann, J.; de Villiers, W.J.S.; Engelbrecht, A.M.
Abstract: The Covid-19 pandemic has spread rapidly across the globe, resulting in more than 3 million deaths worldwide. The symptoms of Covid-19 are usually mild and non-specific, however in some cases patients may develop acute respiratory distress syndrome (ARDS) and systemic inflammation. Individuals with inflammatory or immunocompromising illnesses, such as cancer, are more susceptible to develop ARDS and have higher rates of mortality. This is mediated through an initial hyperstimulated immune response which results in elevated levels of pro-inflammatory cytokines and a subsequent cytokine storm. This potentiates positive feedback loops which are unable to be balanced by anti-inflammatory mediators. Therefore, elevated levels of IL-1β, as a result of NLRP3 inflammasome activation, as well as IL-6 and TNF-α amongst many others, contribute to the progression of various cancer types. Furthermore, Covid-19 progression is associated with the depletion of CD8 + and CD4 + T cells, B cell and natural killer cell numbers. Collectively, a Covid-19-dependent pro-inflammatory profile and immune suppression promotes the optimal microenvironment for tumourigenesis, initiation and immune evasion of malignant cells, tumour progression and metastasis as well as cancer recurrence. There are, however, therapeutic windows of opportunity that may combat both Covid-19 and cancer to improve patient outcomes. Graphical Abstract: ga1 Highlights: Covid-19 promotes a shift from STAT1 to STAT3 signaling, promoting the activation of pro-inflammatory and pro-tumour signaling pathways. Covid-19 promotes excessive production of pro-inflammatory cytokines, e.g. IL-6 and TNF-α, resulting in a cytokine storm. Covid-19 activates the NLRP3 inflammasome, contributing to different phases of malignant disease alongside IL-6 and TNF-α. Covid-19 is associated with decreased T cell, B cell and NK cell and immune exhaustion, enhancing cancer immune evasion. Therapeutic options for Covid-19 and cancer may inhibit tumourigenesis and reduce mortality rates in cancer patients.